Perlindungan Hukum Penerima Fidusia Terhadap Wanprestasi Yang Dilakukan Oleh Pemberi Fidusia Pada Jaminan Fidusia - Syafrida Syafrida; Ralang Hartati; Hasudung Sinaga (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
Fiduciary rights are material rights that provide guarantees. The purpose of writing is to find out the legal protection for fiduciary recipients if the fiduciary giver is in default. The research method used is library research using secondary data in the form of primary legal materials, secondary legal materials and tertiary legal materials. The research is juridical normative. Fiduciary guarantee certificates provide legal protection for fiduciary recipients if the fiduciary giver defaults. The fiduciary recipient can sell on his own power the object that is the object of the fiduciary guarantee for the settlement of his receivables. Irah Irah's fiduciary certificate